A rare presentation of left postaural mastoid osteoma - Sivakumar, E.; Swapna, C. A.; Karanam, Lavanya (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Osteomas are benign slow growing tumors of mesenchymal origin. Most commonly found along the long bones like proximal shaft of femur around 19% followed by tibia around 10% and head and neck osteomas around 0.1 to 1%. We report a rare case of postaural osteoma in a 44 year old female with cosmetic deformity and discuss its differential diagnoses and treatment protocol. A 44-year-old female presented to ear, nose and throat (ENT) outpatient department (OPD) with complaints of swelling in the left postaural region since 25 years gradually increasing in size. On examination, there was a single swelling in the left post aural region measuring about 4×5×3 (cms) hard in consistency and non-tender. Non contrast computerized tomography (CT) of temporal bone showed well defined extracranial dense sclerotic bony lesion arising from mastoid part of left temporal bone likely osteoma. Patient planned for excision and histopathological examination was consistent with osteoma. In conclusion, though osteoma in mastoid bone is a very rare possibility still it should be kept in consideration in the list of differential diagnoses of the tumors of temporal bone. We highlight the need for a careful clinical evaluation supported by radiologic and histopathological investigations which will help in the diagnosis, resulting in better prognosis.